Spillover effects of domestic law enforcement policies (2010)
In the war against drugs, local and state governments in the United States have spent millions of dollars in law enforcement with the aim of reducing drug consumption in their territories. These independent efforts by local or state governments contrast with a more global structure of illegal drug markets where drug lords sell and distribute drugs simultaneously in different territories.